Development of web-based media in instrument analysis college to improve student competence - Sugiharti, Gulmah; Nasution, Haqqi Annazili; Nasution, Mutiara Agustina; Siregar, Muhammad Isa (Jurnal Pendidikan Kimia, 2024)
This research aims to develop and obtain Web-based learning media that meets the eligibility requirements according to BSNP criteria, determine the increase in student competency by using the developed Web-based media and determine the percentage of student responses to Web-based media used in lectures on the topic of instrument analysis. This research method is a research and development method using the ADDIE model. Web-based media was validated by media experts and material experts, then the valid media was presented to 26 Chemistry Education students at Medan State University to see the influence of the Webb media developed and get responses on the web-based media used. The research results show that the Web-based learning media developed meets the BSNP eligibility criteria with an average percentage of 91.25%. The use of Web-based media can increase student competency in lectures on the topic of Instrument Analysis, namely 75% for experimental classes that use Web media and 56% for classes without Web media. Learning outcomes using Webb media are better than without using Webb media and student responses to the use of Webb-based media in lectures Topic evaluation Instrument analysis is very high. Thus, over all the Web-based media developed is good for use in lectures on the topic of Instrument Analysis, to provide students with learning experiences in using the Web.